Telipogon mayoi (Orchidaceae), a new species from the Western Andes of Colombia - Reina-Rodríguez, Guillermo A. (2019)
Telipogon mayoi, from the western Colombian Andes, is proposed as a new species. The species was found in “La Elvira” National Protective Forest in the Yumbo Municipality, one of the oldest protected areas in Colombia, close to the Farallones de Cali National Park, both localities in the Dapa Mountains. Specimens of Telipogon mayoi were previously misidentified as Telipogon lankesteri Ames and T. williamsii P.Ortiz, but detailed analysis of the floral morphology revealed that it is different. Telipogon mayoi is most similar to T. lankesteri but it is characterized by the crenulated margins of the leaves (vs. entire margins), the ovate oblong lip (vs. oblong lanceolate) and furcate setae on the column (vs. simple setae). We provide a description, illustrations, a plate, in situ photographs, a distribution map, and ecological notes.